PERAN MODERASI EXTERNAL ASSURANCE DALAM HUBUNGAN ANTARA ESG DISCLOSURE DAN CREDIT RATING DI INDONESIA (Studi Kasus pada Perusahaan Non-Finansial yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Altsa Kamilatun Nuha; Dwi Ratmono (Diponegoro Journal of Accounting, 2025)
This study aims to provide empirical evidence on the relationship between Environmental, Social, and Governance (ESG) disclosure and corporate credit rating, as well as to examine the role of external assurance as a moderating variable. ESG disclosure is measured using the Global Reporting Initiative (GRI) guidelines through content analysis, while credit ratings are obtained from PEFINDO. The moderating variable in this study is the presence of external assurance on the sustainability report.The study focuses on non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample was selected using a purposive sampling method, resulting in a total of 120 observations. The analytical method employed is ordinal logistic regression with the assistance of EViews 12 software.The results indicate that ESG disclosure has a significant positive effect on a company’s credit rating. In other words, the higher the level of ESG disclosure, the better the credit rating awarded. However, the findings also reveal that the presence of external assurance significantly weakens this positive relationship, suggesting that assurance is not always perceived as an additional signal of credibility by credit rating agencies.